Pengaruh Knee Support terhadap Risiko Jatuh pada Lansia Ditinjau dari Keseimbangan Statik dan Keseimbangan Dinamik - Mandasari, Cica Tri; Firmanurulita, Fadhila (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: The risk of falls among the elderly was a significant public health issue, as it could lead to serious injuries, decreased quality of life, and increased healthcare costs. One of the main contributing factors to falls was the decline in knee joint stability and balance function. The use of simple orthoses such as knee supports was suspected to provide additional stabilization and enhance proprioceptive input, thereby improving balance and reducing the risk of falls. Objectives: This study aimed to determine the effect of knee support use on the risk of falls in the elderly in terms of static and dynamic balance. Methods: This study used a quasi-experimental design with a one-group pre-test and post-test approach. The sample consisted of 15 elderly individuals at the Posyandu Lansia in Dusun Pepe, Kelurahan Gedongan. The instrument used to measure static balance was the Berg Balance Scale (BBS), and for dynamic balance, the Timed Up and Go (TUG) test was used. Data were analyzed using a Paired T-Test and Wilcoxon, preceded by a normality test using the Shapiro-Wilk method. Results: The results of the pairedsample t-test and wilcoxon test showed that the significance value was less than 0.05. There was an increase in BBS scores and a decrease in TUG time after the knee support intervention was given. Knee support had an effect on the risk of falls in the elderly in terms of both static and dynamic balance. All research participants were female. Conclusion: This study showed that knee support intervention affected the risk of falls in the elderly as seen from improvements in static and dynamic balance. Keywords: Elderly, Fall risk, Knee support, Balance